Analisis korelasi tingkat pendidikan dan status ekonomi terhadap kesejahteraan sosial dengan tingkat pendapatan sebagai contingency variable di kabupaten labuhanbatu - Nurintan Asyiah Siregar (JURNAL PUNDI, 2018)
Social Welfare is a common goal to be achieved. Therefore there is a need to increase the quality of education in the district of Labuhanbatu. Because with a low level of education will result in social welfare and low in support with low economic status and low income levels again. A high level of crime that occurred in the district of labuhanbatu caused by the low income level that effect cause social welfare disrupted. For long-term author want to achieve is able to formulate a policy that can improve tarap community living that has a low level of education so that the level of kriminilitas can minimalize. Special targets to be achieved in this research is the regional government can know exactly how the situation of social welfare that occurs in the rural areas. The method to achieve that goal is to provide skills training and motivation to be increased education kejenjang higher. This research uses the primary data obtained or collected directly from the source of the data through the spread of a list of questions (questionaire) and interview (interview). Keywords: The level of education, Economic status, Social Welfare, Income Level